Case report: Cutaneous pseudolymphoma caused by a Leishmania infantum infection in a patient treated with anti-TNF antibody for plaque psoriasis - Scholl, Sarah; Schuster, Daniel; Technau-Hafsi, Kristin; Stete, Katarina; Rieg, Siegbert; May, Annette M.; Bogdan, Christian; Schauer, Franziska (Frontiers in Medicine, 2022)
Adalimumab is approved for the treatment of psoriasis, which affects up to 2% of the population. Here, we present a middle-aged Italian man with long-term history of plaque psoriasis and psoriasis arthropathica. During the therapy with methotrexate and adulimumab he developed nodules and ulcers within the psoriatic plaques that were found to be positive for Leishmania infantum. After discontinuation of the anti-TNF-treatment, the infection resolved without anti-leishmanial therapy, which underlines the critical role of TNF for parasite control.